Conservative thinkers the key contributors to the political thought of the modern Conservative Party - Garnett, Mark 1963-; Hickson, Kevin (Manchester Univ. Press, 2009)
Includes chapters on Harold Macmillan; Rab Butler and the One Nation Group; Quintin Hogg, Lord Hailsham; Enoch Powell; Angus Maude; Keith Joseph; the Traditionalists; Ian Gilmour and the Wets; John Redwood; and David Willettts
Includes bibliographical references (p. [179]-186) and index
Keywords: Conservative Party (Great Britain) / History / 20th century; British Conservative and Unionist Party; Geschichte 1900-2000; Political science / Great Britain / Philosophy / History / 20th century; Intellectuals / Political activity / Great Britain / History / 20th century; Geschichte; Philosophie; Politische Wissenschaft; Politisches Denken; Großbritannien